Shortcomings of Rapid Clinical Information Dissemination: Lessons From a Pandemic. Issue 3 (June 2021) - Lau, K.H. Vincent; Anand, Pria
Abstract : The coronavirus disease 2019 (COVID-19) pandemic has led to an acceleration of clinical information dissemination to unprecedented speeds, a phenomenon only partially explained by formal efforts of the scientific community. These have ranged from the establishment of open-source platforms for review of article preprints to the elimination of journal paywalls for COVID-19–related publications. In addition, informal efforts that rely on various modern media platforms that promote, repackage, and synthesize information have played substantial adjunctive roles, many of which did not exist during the severe acute respiratory syndrome pandemic of 2003. Although these latter efforts have greatly bolstered the speed of knowledge dissemination, their unregulated nature subjects them to risk for facilitating the spread of misinformation. In our opinion, the role of modern media in influencing clinical knowledge dissemination was not adequately examined even before the pandemic and therefore remains largely unchecked. In this article, we examine the spread of information in the field of COVID-19 and neurologic disorders, develop a simple model that maps various modern media tools on to the dissemination pipeline, and critically examine its components. Through this exercise, we identify opportunities for the scientific community to regulate and safeguard the clinical knowledge dissemination process, with implications both for the pandemic and beyond.